A large-scale study across the avian clade identifies ecological drivers of neophobia - ManyBirds Project; Miller, Rachael; Šlipogor, Vedrana; Caspar, Kai R.; Lois-Milevicich, Jimena; Soulsbury, Carl; Reber, Stephan A.; Mettke-Hofmann, Claudia; Lambert, Megan; Ashton, Benjamin J.; Auersperg, Alice M. I.; Bateson, Melissa; et al. (PLOS Biology, 2025)
Neophobia (the aversive response to novelty) varies considerably across species and individuals, and can impact adaptability and survival. This study assesses neophobia in 1400 subjects from 136 bird species across 25 orders, identifying phylogenetic influences and broad ecological drivers of neophobia.